Zeolites - Useful Minerals 2016
DOI: 10.5772/63792
|View full text |Cite
|
Sign up to set email alerts
|

Upscaling of Zeolite Synthesis from Coal Fly Ash Waste: Current Status and Future Outlook

Abstract: Coal fly ash has been recognised as suitable feedstock for zeolite synthesis, and with this discovery, there has been much literature produced over the years on various synthesis processes with a view to address the disposal problems associated with fly ash wastes. The different synthesis processes can be divided into a pre-synthesis activation with an alkali solution and a hydrothermal synthesis of heating the resulting aluminosilicate gel. However, the challenge lies in up scaling the synthesis to allow prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
(117 reference statements)
0
9
0
Order By: Relevance
“…Zeolite X was present in the samples prepared from both distilled water and wastewater NaOH solutions ( Figure 2 b,c), however, the XRD patterns indicated that the synthesis was more efficient in distilled water. This can be explained by the complex chemical composition of wastewater [ 49 ] and high Cl − ion concentration. As proven in previous research [ 46 ], crystallization of the zeolite phase is favored by the absence of Cl − ions in the solution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zeolite X was present in the samples prepared from both distilled water and wastewater NaOH solutions ( Figure 2 b,c), however, the XRD patterns indicated that the synthesis was more efficient in distilled water. This can be explained by the complex chemical composition of wastewater [ 49 ] and high Cl − ion concentration. As proven in previous research [ 46 ], crystallization of the zeolite phase is favored by the absence of Cl − ions in the solution.…”
Section: Resultsmentioning
confidence: 99%
“…For all the conditions, an increase in the intensity of characteristic peaks at subsequent samples was observed, indicating further progress of the zeolitization process. Depending on the reaction conditions, different and mixed products of synthesis are described in numerous reports [ 49 , 50 ]. Extending the heating time was identified as a sufficient factor to change the dominant zeolite phase in the collected samples, as well as to speed up the zeolitization process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CFA is specified in two classes F and C according to the international standard ASTM C618 regarding its chemical composition from the point of view of the suitability of this raw material for production of cement [9]. Smart utilization of coal fly ash is the processing of zeolites by alkaline conversion processes [10,11]. CFA-based zeolites with a controllable size of the constituent crystallites of the order of nanosizes and with a uniform distribution of the metal oxide phases transferred into the zeolite matrix from the raw ash as nanoparticles can be considered as nanocomposites unlike their pure synthetic analogies.…”
Section: Introductionmentioning
confidence: 99%
“…The main methods used to obtain a specific zeolite as a unique crystalline phase from coal FA are alkaline fusion and two‐stage synthesis that involves silica extraction, but only few studies have reported a unique crystalline phase product by a direct zeolitization method. The current challenge lies in scaling up the synthesis to allow production on a commercial scale …”
Section: Introductionmentioning
confidence: 99%